The Role of Child Characteristics and Peer Experiences in the Development of Peer Cooperation. Issue 3 (4th January 2015) - Endedijk, Hinke M.; Cillessen, Antonius H. N.; Cox, Ralf F. A.; Bekkering, Harold; Hunnius, Sabine
Abstract Cooperation with peers is challenging for young children, and there are large individual differences in the development of cooperation. The roles of child characteristics and peer experiences for peer interaction during free play have been studied extensively, but it is unclear which factors predict young children's successful cooperation at different points in development. In this study, 2‐, 3‐, and 4‐year‐old children were observed during a peer cooperation task. Both their interactive behavior and cooperation success were examined, and the association of these variables with child characteristics and peer experiences was explored. Results showed that successful peer cooperation increased with age. Moreover, early individual differences in peer cooperation were related to temperamental characteristics, and, among older children, the rate of cooperation was related to prior peer experience.